The Rainbow Dichotomy: Evaluating Perceptions of ’Rainbow-Washing’ in Pride Month Marketing Campaigns Among Lgbtq+ and Heterosexual Consumers in Thailand - Paklapas, Minjade; Punyalikit , Rueanglada; Joneurairatana, Eakachat (Journal of Roi Kaensarn Academi, 2024)
This research aims to critically evaluate the perceived authenticity of Pride Month marketing campaigns in Bangkok, Thailand, as well as the willingness for multiple cohorts of consumers to buy products advertised by the LGBTQ+ or Pride initiatives. The population of interest is LGBTQ+, heterosexual, and heterosexual people who are uninterested or opposed to the rights benefited by LGBTQ+ people. A total of 383 participants were stratified and randomly sampled, so that each group is represented. Research instruments consist of structured and unstructured questionnaires and in-depth interview guides for quantitative and qualitative data. Descriptive statistics, inferential statistics (such as ANOVA and regression analysis), and thematic analysis were applied to the statistical analysis of research questions by descriptive measures, ANOVA, and regression analysis, in a simple and effective manner. This finding shows that different demographic groups have radically different perceptions about the authenticity of Pride Month marketing. In general, LGBTQ+ people and allies find more authenticity in these campaigns than indifferent or opposed to LGBTQ+ rights, who often demonstrate skepticism for fears that the campaigns are ’rainbow washing.’ Response to emotional experiences represented through affect clues reveals how purchase willingness is driven by positive emotions across LGBTQ+ populations and possessed by negative emotions in alternative populations. What the study points out, most importantly, is that marketing is about enabling that authenticity and building trust in something consumers believe in, which in this case is supporting LGBTQ+ rights. Brands should work closely with LGBTQ+ communities and create campaigns that are LGBTQ+ inclusive, and avoid superficial practices which will repel potential audiences.